PASSIVE POSITIONING METHOD USING DISTANCE MEASURING EQUIPMENT AND AUTOMATIC DEPENDENT SURVEILLANCE-BROADCAST DATA - Ostroumov, Ivan (Proceedings of National Aviation University (archive), 2018)
Purpose: The represented research results are aimed to develop a new positioning method that uses DME signals in space and ADS-B messages from airspace users. Proposed approach of positioning is based on passive signal collection and analysis. One aircraft interacting with two different DMEs is a source of three hyperbolic lines of location, crossed point of which can indicate passive user location. Methods: Presented approach is grounded at time difference of arrival methods, statistical methods of error estimation and computer-based simulation at verification stage of development. Results: Proposed method of aircraft coordinates detection can reduce the load on DME ground network, since it focuses on the passive observation of DME signals that are present in airspace. Discussion: The approach can be implemented in algorithms of flight management system as an alternative positioning method to existing ones.